Grid integration of wind power generators - Moey, Jun Xin (2012)
With global warming and sea levels reaching an unprecedented level, mankind has begun to realise the disastrous effects of burning fossil fuels on Earth. To reduce the impact of climate changes, a huge reduction of greenhouse gases emission is necessary. In the search for alternative energies, wind power is gaining success as a clean and abundant alternative energy, so much that it has evolved into large scale wind farms for energy harnessing. In this project, a new configuration of the doubly fed induction machine (DFIG) is